Education Using Animated Videos and Leaflets on Preventing The Risk of Nomophobia in High School Adolescents - Heni Nurhaeni; Clarisa Setyo Putri; Reni Chairani (Poltekkes Kemenkes Semarang, 2023)
Background: Nomophobia is an experience due to not being able to use a mobile phone. Nomophobia can be caused by excessive use of mobile phones with a duration of 3 hours/day, and most of the sufferers are junior high school students. Purpose: To describe the effectiveness of education using animated videos and leaflets on preventing the risk of nomophobia among junior high school adolescents in South Jakarta.Methods: Quasi-experimental with a pretest-posttest used in control group to determine the effectiveness of adolescent education with the risk of nomophobia at SMPN 218 Jakarta and SMP PGRI 12. The sample size was 45 respondents.Results: There was a significant difference in reducing the risk of nomophobia before and after interventions, in the intervention group with. A significant decrease also occurred between the intervention group and the control group before and after the intervention with a difference mean score (6.33 points). The difference between the two groups was substantially significant to the possibility of reducing the incidence of nomophobia in adolescents with a value of p-0.041.Conclusion: Using different educational methods, such as inviting respondents to do positive thing to reduce the perceived gadget addiction.